Rekontruksi Citra Tomografi Sinar-X Flouresens 2D Berbasis Teknik Radiografi Digital Menggunakan Bahasa Pemrograman Matlab 7.1 - M.Si, Sumariyah; Muhlisin, Zainul; Setiawati, Evi (BERKALA FISIKA, 2010)
This research has been done Recontructing of 2D X-ray Flouresense Tomographic Imaging Basis on Digital Radiograhy Technique using MATLAB 7.1 Programming The research uses an unit Computed Radiografi, a rotated obyect and a reconstruction programme imaging. The shape of rotated object is prisma which made of acrylic, lenght 18 cm and size sisi 6 cm. The prismacan rotate continue and as cor of the rotatd obyek uss asylinder still. Recontruction 2D tomographic imaging build from 25 rotatd object radiograf imaging result of expose Computed Radiografi with expose factor constant ang interval increasing rotated angle7,50 . The reconstruction programme 2D Tomographic consist of the cropping programme which produces 25 slice rotatd obyect forming sinogram and the programm Transformation invers Radon. The result of 2D Tomographic reconstruction in this rsearch obtain cross-sectionalprisma imaging is circle in the triangle sisi same imaging which habrur. Keywords: recontruction, tomography and radiography